Review on synthesis gas production in a downdraft biomass gasifier for use in internal combustion engines in Nigeria - P.E. Akhator; A.I. Obanor (Journal of Applied Sciences and Environmental Management, 2018)
This paper presents a review on the possibility and potential of synthesis gas production and its utilization as an alternative fuel for internal combustion engines (ICE) in Nigeria. Information on numerous experimental studies and demonstrations on downdraft biomass gasification for synthesis gas production as well as the potential use of synthesis gas as fuel for ICE applications were assessed. The review reveals that there are abundant biomass resources in Nigeria and there is a great potential to produce synthesis gas from these sources using downdraft gasifier as preferable technology.